Fundamental Concepts of Mathematics - Leung, Kam-tim (Book collections on Project MUSE., 1988)
Basic concepts of number theory are discussed. Topics include set theory, mathematical induction, com-binatorics, arithmetic, real numbers, limit and convergence, and complex numbers.